How intra-organizational social capital influences employee performance. Issue 9 (10th October 2016) - Ben Hador, Batia
Abstract : Purpose: The purpose of this paper is to contribute to a growing research field on the subject of intra-organizational social capital (IOSC) and its effects on employee job performance. Design/methodology/approach: Data were collected from a sample of 209 employees in community centers. The variables that were specified are IOSC, vigor, self-efficacy, and a supervisor report regarding employee performance. Findings: The results indicate a mediation-moderation model in which the connection between IOSC and employee performance is mediated by vigor and moderated by self-efficacy. Research limitations/implications: Although the sample includes employees from a single organization, collecting data from different sources within the organization permitted to overcome this limitation. Mainly, the current findings emphasize the importance of the interaction between environment and personality. Practical implications: Creation and preservation of IOSC in organizations increases the employee vigor and can serve to upgrade performance. Originality/value: The important role of IOSC in organizations has been confirmed. Furthermore, the combination between supportive environment and personality traits can foster employee performance.